Financial drivers of the euro area business cycle: A DSGE-based approach - Dominik Hirschbühl; Georgi Krustev; Grigor Stoevsky (European Central Bank (ECB), 2020)
We estimate a modified version of the "Financial Business Cycles" model originally developed by Iacoviello (2015) in order to investigate the role played by financial factors in driving the business cycle in the euro area. In the model, financial shocks such as borrower defaults, collateral shocks and credit supply effects amplify economic downturns by reducing the flow of credit from banks to the real sector. In this novel application to the euro area, we introduce capital reallocation inefficiency, an innovation to the original set-up which allows for more realistic effects of entrepreneur defaults on economic activity. Our results suggest that financial factors, as captured by this model, played a smaller role in the euro area throughout the double-dip recession than in the United States during the 2008-09 global financial crisis. In a scenario on second-round effects implied by potential NFC loan losses due to the COVID-19 pandemic, we find large financial amplification risks to real economic activity
Keywords: E32; E44; E47; 330; DSGE; Bayesian estimation; housing; financial frictions